Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300543
|View full text |Cite
|
Sign up to set email alerts
|

Social Reflections on Fitness Tracking Data

Abstract: Wearable activity trackers can encourage physical activity (PA)-a behavior critical for preventing obesity and reducing the risks of chronic diseases. However, prior work has rarely explored how these tools can leverage family support or help people think about strategies for being active-two factors necessary for achieving regular PA. In this 2-month qualitative study, we investigated PA tracking practices amongst 14 families living in low-income neighborhoods, where obesity is prevalent. We characterize how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Some researchers have noted that much of the research on activity-related personal informatics doesn't take into account the social network that is essential for the longer-terms success of the tracking technology [62]. Based on a 2-month study with 14 low-income families, Saksono et al outline how the current practice of using activity trackers is designed to be an individual activity, with few families engaging in social discussions of the data.…”
Section: Motivation Strategies and Older Adultsmentioning
confidence: 99%
“…Some researchers have noted that much of the research on activity-related personal informatics doesn't take into account the social network that is essential for the longer-terms success of the tracking technology [62]. Based on a 2-month study with 14 low-income families, Saksono et al outline how the current practice of using activity trackers is designed to be an individual activity, with few families engaging in social discussions of the data.…”
Section: Motivation Strategies and Older Adultsmentioning
confidence: 99%
“…Nevertheless, we could argue that data recorded by most activity trackers and self-monitoring applications currently is still of little value in facilitating meaningful reflection on lifestyle. In a previous study it was found that the participants from a low SES neighborhood rarely analyzed their self-monitoring experiences to derive insight about the meaning of data for their well-being ( 68 ). One example of providing meaningful data is a smoking app that displays, besides the number of days without cigarettes, also the amount of money the person has saved by not smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Technology can support only to mid-conflict solutions, but also inter-conflict reflection. Current applications demonstrate technology's versatility in representing information for social reflection [51,63,76,78]. In contrast to existing mid-conflict approaches, we posit that promoting deeper reflections in-between conflict occurrences may support the development of crucial transformative insights and approaches for handling nontrivial conflict in close relationships [11].…”
Section: Introductionmentioning
confidence: 92%